After the Philosophy of Mind: Replacing Scholasticism with Science. - Chemero, Anthony; Silberstein, Michael (Philosophy of Science, 2008)
We provide a taxonomy of the two most important debates in the philosophy of the cognitive and neural sciences. The first debate is over methodological individualism: is the object of the cognitive and neural sciences the brain, the whole animal, or the animal--environment system? The second is over explanatory style: should explanation in cognitive and neural science be reductionist-mechanistic, interlevel mechanistic, or dynamical? After setting out the debates, we discuss the ways in which they are interconnected. Finally, we make some recommendations that we hope will help philosophers interested in the cognitive and neural sciences to avoid dead ends